Evaluation of Ambient Vibration Test Method for Historic Wooden Buildings Based on the Rigid Diaphragm Assumption. Issue 2 (1st May 2016) - Kim, Hongjin; Ko, Young-Nam; Cho, Jae-Mo
Abstract: To retrofit historic wooden buildings to improve their seismic and wind resistance, the precise structural assessment to such loads is essential. However, little research has been done in Korea on the ambient vibration test (AVT) of historic wooden buildings for the collection of dynamic characteristics and the corresponding structural assessment. The reason for this is that, for wooden buildings, unlike reinforced concrete (RC) and steel buildings, a systematic in situ AVT method has not been established. In this paper, an in situ AVT method is presented for historic wooden buildings based on the assumption that rigid diaphragm action plays a role in the structural responses of wooden buildings. This assumption is reasonable when the roof and rafters restrain the rotation of columns, as do slabs in RC and steel buildings. The proposed method was employed in an evaluation of the dynamic characteristics of a small traditional wooden building to assess its applicability. The method was also applied to in situ AVT of eight historic wooden buildings that are designated as national treasures in Korea.